Students’ Higher Order Thinking Profiles in Completing Contextual Problems on Slerek Boat Used by Fishermen in Muncar Banyuwangi - Hajar Istiqomah; Titik Sugiarti; Lioni Anka Monalisa; Toto’ Bara Setiawan; Erfan Yudianto (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2019)
Higher Order Thinking Skills (HOTS) is an ability that can create students in critical and creative individuals. The ways that can be used to reveal students' high-level thinking skills by using contextual problems in learning. The purpose of this study was to describe the profile of high order thinking of 8th-grade students in solving contextual problems regarding slerek boat. This research is a type of descriptive research with a qualitative approach. The research subjects were 8thH grade students of SMPN 1 Muncar, which amounted to 28 students. Data retrieval using test questions and interview activities. From the results of data collection, the results show that the ability of 8thH grade students tends to be able to solve questions at the evaluation level. This can be seen from the results of the test questions where there is 1 student who can solve the question of creation level (C6), 22 students can solve the question of the level of evaluation (C5) and 5 students can solve the level of analysis (C4). Based on the results of interviews, students who can solve the question level C5 have good ability in analyzing problems can explain the settlement process both orally and in writing, besides that it’s also able to make a hypothesis and test the hypothesis made previously